2006
DOI: 10.17221/6234-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

DNA-markers for resistance to common bunt transferred from Aegilops cylindrica Host. to hexaploid wheat

Abstract: Common bunt, caused by Tilletia caries (DC.) Tul., is widespread disease of wheat (Triticum aestivum L.) that causes serious yield reduction and loss of quality of this crop. Majority of Ukrainian wheat varieties are susceptible to bunt. It is necessary to search for sources of effective resistance genes.Aegilops cylindrica (2n = 28; genome CCDD) is a source of genes for some pest resistance in wheat Bochev et al. (1982). Ae. cylindrica carries resistance to leaf rust, stem rust, fusarium, septoria, powdery mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In addition, introgressions of common bunt resistance factors from rye ( Secale cereale , Martynov and Dobrotvorskaya 2003), triticale (Ciuca 2011), barley ( Hordeum vulgare , Rubiales et al 2001), Aegilops glaucum (Martynov and Dobrotvorskaya 2003), Ae. cylindrica (Galaev et al 2006), Ae. ventricosa (Babayants et al 2006), Triticum erebuni (Babayants et al 2006) and Agropyron intermedium (Goates 1996) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, introgressions of common bunt resistance factors from rye ( Secale cereale , Martynov and Dobrotvorskaya 2003), triticale (Ciuca 2011), barley ( Hordeum vulgare , Rubiales et al 2001), Aegilops glaucum (Martynov and Dobrotvorskaya 2003), Ae. cylindrica (Galaev et al 2006), Ae. ventricosa (Babayants et al 2006), Triticum erebuni (Babayants et al 2006) and Agropyron intermedium (Goates 1996) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these genes, 'alien' sources of resistance also have been used in breeding, for example, BtZ originating from Agropyron intermedium (Host) P. Beauv. (Goates 1996), or resistance derived from Aegilops cylindrica Host (Galaev et al 2006), and other grasses .…”
Section: Introductionmentioning
confidence: 99%
“…Both the incidence and severity of common bunt have been controlled in the Canadian prairies, largely by introgressing resistance genes such as Bt10 and Bt8 (Menzies et al, 2006;McCallum and DePauw, 2008;Hiebert et al, 2011). Quantitative trait loci (QTLs) associated with resistance to common bunt have also been reported on chromosomes 1B and 7A (Galaev et al, 2006;Fofana et al, 2008;Wang et al, 2009). Resistance to common bunt has remained generally stable against shifts in virulence in the pathogen, but the vulnerability of such major genes through intense selection pressure on the pathogen is always a concern (Wang et al, 2009).…”
mentioning
confidence: 99%
“…Resistance to common bunt has remained generally stable against shifts in virulence in the pathogen, but the vulnerability of such major genes through intense selection pressure on the pathogen is always a concern (Wang et al, 2009). Quantitative trait loci (QTLs) associated with resistance to common bunt have also been reported on chromosomes 1B and 7A (Galaev et al, 2006;Fofana et al, 2008;Wang et al, 2009). Tan spot, caused by P. tritici-repentis, is another economically important disease of wheat in Canada and other major wheat-growing countries (Faris et al, 1997;Friesen and Faris, 2004).…”
mentioning
confidence: 99%